UNDERSTANDING DISTRIBUTION THROUGH QUR’AN AND HADITH INTERPRETATIONS - Dissy Farrel Dwiky Maulana; Ahmad Ardi Firmansyah; Candni Aulia Fasya; Putri Novita Sari; Berlian Rizky Defina; Nita Putri Salsabilla; Nabila; Taufiq Kurniawan (Jurnal Media Akademik (JMA), 2026)
Distribution is a central issue in Islamic economics, which aims to achieve collective welfare. However, distribution is often narrowly understood as the transfer of goods and services from producers to consumers, rather than as the fair allocation of wealth. This study analyzes verses from the Qur'an and Hadith related to the ethics of wealth distribution to identify the principles promoted in Islam. This article uses a literature review method with a library research approach, with the main sources taken from the Qur'an and Hadith, supported by relevant academic literature such as journal articles. The findings show that Islamic distribution ethics emphasize justice and equality, brotherhood and compassion, and social solidarity. Instruments such as zakat, infaq, sadaqah, and waqf play a strategic role in realizing wealth equality while reducing economic inequality in society. In addition, the Qur'an highlights the importance of prioritizing spiritual well-being over material interests in economic activities. In conclusion, ethical distribution in Islam serves as a fundamental pillar for fostering social balance and promoting holistic human prosperity.